The Effect Of Profit Perception On Intention To Use X Fintech: The Role Of Security As Mediation And Ease Of Use As Moderation - Bahri, Yanu Yusabbitul; Damayanti, Riska; Anggraini, Rini; Lestari, Amanda; Erivia, Fadisa Dera Wisnu; Noviansyah, Rizky Ramadhan (Lentera Ilmu Nusantara, 2024)
The development of digital technology has transformed the financial sector with the emergence of financial technology (fintech). This study aims to analyze the influence of profit perception on the intention to use fintech, with security as the mediating variable and ease of use as the moderation variable. The research method used is a quantitative approach with accidental sampling techniques. Data was collected through a questionnaire from 100 respondents who used fintech applications. Data analysis using Partial Least Square (PLS) with the help of SmartPLS 3.0 software. The results of the study show that the perception of profit has a positive effect on the intention to use fintech, with security mediating the relationship. Ease of use has also been proven to moderate the influence of profit perception on the intention to use fintech. These findings provide new insights for the development of more effective fintech marketing strategies by considering aspects of security and ease of use.